Impact of the Circadian Clock on UV‐Induced DNA Damage Response and Photocarcinogenesis1. (18th December 2016) - Dakup, Panshak; Gaddameedhi, Shobhan
Abstract: The skin is in constant exposure to various external environmental stressors, including solar ultraviolet (UV) radiation. Various wavelengths of UV light are absorbed by the DNA and other molecules in the skin to cause DNA damage and induce oxidative stress. The exposure to excessive ultraviolet (UV) radiation and/or accumulation of damage over time can lead to photocarcinogenesis and photoaging. The nucleotide excision repair (NER) system is the sole mechanism for removing UV photoproduct damage from DNA, and genetic disruption of this repair pathway leads to the photosensitive disorder xeroderma pigmentosum (XP). Interestingly, recent work has shown that NER is controlled by the circadian clock, the body's natural time‐keeping mechanism, through regulation of the rate‐limiting repair factor xeroderma pigmentosum group A (XPA). Studies have shown reduced UV‐induced skin cancer after UV exposure in the evening compared to the morning, which corresponds with times of high and low repair capacities, respectively. However, most studies of the circadian clock–NER connection have utilized murine models, and it is therefore important to translate these findings to humans to improve skin cancer prevention and chronotherapy. Abstract : Exposure of the skin to sunlight causes DNA damage. As a result, the body responds to this environmental insult through various defensive mechanisms including the nucleotide excision repair, which is regulated by the circadian clock. Hence, the time‐of‐the‐day and maintaining a healthy circadian rhythm are important in determining the mutagenic and carcinogenic potential of UVR insult to the skin.